KARAKTERISTIK PEMIMPIN TERHADAP PERILAKU KEPEMIMPINAN, KINERJA BAWAHAN, DAN PERTUMBUHAN USAHA INDUSTRI KECIL - Ilham Thaief (Journal of Management and Business, 2010)
The aim of this research is to examine the influence of leaders’ characteristics (motivation, talent, knowledge, and skill) on their own behavior (consideration and initiation structure), the performance of their subordinates, and small business industry growth; and to know which of these factors are most dominant. This research was carried out by conducting interviews and distributing questionnaires to 260 company leaders in the city of Makassar and the regencies of Maros and Gowa. Sample selection was conducted using proportional accidental random sampling. Microsoft Excel, SPSS, and AMOS were used in data processing. The results show that in general leadership characteristics influence both the performance of subordinates and growth of the small business industry. In specific, the motivation factor directly, positively, yet insignificantly influences consideration, while negatively and significantly influencing initiation structure. The talent factor directly, positively and significantly influences both consideration and initiation structure. The knowledge factor directly, positively, yet insignificantly influences both consideration and initiation structure. The skill factor directly and significantly influences consideration and initiation structure. Consideration and initiation structure directly, positively, and significantly influences the performance of subordinates which in turn directly, positively, and significantly influences growth of the small business industry. The dominant factor influencing consideration is the leader’s skill followed by talent, motivation, and knowledge. The dominant factor influencing initiation structure is the leader’s skill followed by talent, motivation, and knowledge. The dominant factor influencing the performance of subordinates is consideration followed by initiation structure, skill, motivation, and knowledge. The dominant factor influencing small business industry growth is the performance of subordinates followed by consideration, initiation structure, skill, talent, motivation and knowledge